Notch Ligand Delta-Like 1 Is Associated With Loss of Vascular Endothelial Barrier Function - Moll, Maximilian; Reichel, Konrad; Nurjadi, Dennis; Förmer, Sandra; Krall, Lars Johannes; Heeg, Klaus; Hildebrand, Dagmar (Frontiers in Physiology, 2021)
Vascular leakage associated with vascular endothelial cell (vEC) dysfunction is a hallmark of sepsis. Causative for the decreased integrity of the vascular endothelium is a complex concurrence of pathogen components, inflammation-associated host factors and the interaction of vECs and activated circulating immune cells. One signaling pathway that regulates the integrity of the vascular endothelium is the Notch cascade, which is activated through binding of a Notch ligand to its respective Notch receptor. Recently we showed that the soluble form of the Notch ligand Delta-like 1 (sDLL1) is highly abundant in the blood of patients with sepsis. However, a direct connection between DLL1-activated Notch signaling and loss of vEC barrier function has not been addressed so far. To study the impact of infection-associated sDLL1, we used Human umbilical vein cells (HUVEC) grown in a trans-well system and cocultured with blood. Stimulation with sDLL-1 induced activation as well as loss of endothelial tight structure and barrier function. Moreover, LPS- stimulated HUVEC activation and increase of endothelial cell permeability could be significantly decreased by blocking DLL1-receptor binding and Notch signaling, confirming an involvement of the cascade in LPS-mediated endothelial dysfunction. In conclusion, our results suggest that during bacterial infection and LPS recognition, DLL1-activated Notch signaling is associated with vascular permeability. This finding might be of clinical relevance in terms of preventing vascular leakage and severity of sepsis.